If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(y + -10) = -16 Reorder the terms: y(-10 + y) = -16 (-10 * y + y * y) = -16 (-10y + y2) = -16 Solving -10y + y2 = -16 Solving for variable 'y'. Reorder the terms: 16 + -10y + y2 = -16 + 16 Combine like terms: -16 + 16 = 0 16 + -10y + y2 = 0 Factor a trinomial. (2 + -1y)(8 + -1y) = 0Subproblem 1
Set the factor '(2 + -1y)' equal to zero and attempt to solve: Simplifying 2 + -1y = 0 Solving 2 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1y = 0 + -2 -1y = 0 + -2 Combine like terms: 0 + -2 = -2 -1y = -2 Divide each side by '-1'. y = 2 Simplifying y = 2Subproblem 2
Set the factor '(8 + -1y)' equal to zero and attempt to solve: Simplifying 8 + -1y = 0 Solving 8 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1y = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1y = 0 + -8 -1y = 0 + -8 Combine like terms: 0 + -8 = -8 -1y = -8 Divide each side by '-1'. y = 8 Simplifying y = 8Solution
y = {2, 8}
| y(y-10)=16 | | y^2=-11y | | (z-5)(z+4)=52 | | b(b+3)=28 | | x^3+x^2-25x-25=0 | | 0.5(3-2x)=0.3(3-x) | | 255+987= | | 3x+9=x+27 | | 4t^2+2t+1=0 | | 2x+x(x-3)=0 | | m^2+11=6m | | 10p-p^2+2=0 | | m^2+11=gm | | 5x^2=13x-6 | | 2k-(8k+4)=-2k+6 | | t^2-4t=21 | | 0.75(4x+12)=-20 | | v-4.025=-1.9024 | | -90=18-12v | | -8d-29=-77 | | 16+3d=d | | 25-9p=-11 | | y-16=23 | | y(3n^3-3n^2+n+1)=0 | | 8=-4k^2 | | p^3+9p^2+4p+36=0 | | ln(2x+5)+ln(x-5)-2ln(x)=0 | | 3x+5(x-1)=27 | | 0.3(3w-6)=-0.5(2w-4) | | 3x+3=15whatsx | | 8p-12p=0 | | x^3+2x^2+5x-4=0 |